Penerapan Metode Simple Additive Weighting (SAW) Untuk Ketepatan Pemilihan Topik Skripsi Mahasiswa Program Studi Teknik Informatika UNHASY - Zakiya Waliyulloh, M.; Imam Agung, Achmad; Kistofer, Terdy (Inovate, 2022)
Graduating on time is the desire of all students, to achieve graduation, students must work on a thesis as a requirement for graduation at higher education in order to obtain a bachelor's degree in accordance with their scientific field. In taking thesis, there are often students who are confused about choosing the thesis topic to take. To overcome this problem, this research was taken as a solution that utilizes computer technology and uses the Simple Additive Weighting (SAW) method as a decision support system for the accuracy of selecting thesis topics in the Informatics Engineering Study Program at the Hasyim Asy'ari Tebuireng University, Jombang. From the application system, the accuracy of selecting the thesis topic is that the user must first see the student grade data from semester one to semester six and the results of the interest questionnaire that has been made, after it is known that it will be processed with an application system that uses the SAW method as decision making, in the calculation process of In this system, the final result is an alternative Web services for e-Business (A1) with a value of 0.99, and the results obtained from application testing using 30 samples of student data obtained an average percentage of accuracy of the accuracy of the results of 75% of the student thesis topic selection. Keywords: SAW, Decision Support System, Thesis Topics.